Kinerja peternak sapi perah PFH (Studi kasus pada anggota Koperasi Agro Niaga) di Kecamatan Jabung Kabupaten Malang - Kartika Budi Utami; Lilik Eka Radiyati; Puguh Surjowardojo (Faculty of Animal Science, Universitas Brawijaya, 2014)
The objective of this research was to describe performance of farmers as member of KAN Jabung. The research materials were 94 farmers in several milk collection stations located in Sidomulyo (n=29 farmers), Slamparejo (n=30 farmers) and Kemiri (n=35 farmers). The data was collected by observation, interview guided by a questionnaire. The result showed that generally farmers had fairly good performance (score=2) on implementing feeding procedures, good performance (score=3) on applying sanitation procedures and fairly good performance (score=2) on implementing milking and post milking procedures. Keywords: dairy farmer, milking practices, cooperative